2021
DOI: 10.53893/ijrvocas.v1i3.63
|View full text |Cite
|
Sign up to set email alerts
|

Online English Learning for Mechanical Engineering Students during the Pandemic: Challenges and Suggestions

Abstract: The COVID-19 pandemic has brought changes to the whole world. This pandemic also has an impact on the learning system in Indonesia. From the previous face-to-face learning to online learning, including for English courses. This study aims to elaborate on what challenges were faced by students during online English learning, and what suggestions were given to face and solve these challenges. The object of this research was the first semester students of Mechanical Engineering at the Tanah Laut State Polytechnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…The outbreak forces many educational institutions to shift from traditional classroom-based learning to online learning [1] and hybrid learning is still maintained and conducted nowadays. Online video conferences have emerged as one of the most popular ways of providing face-to-face learning in a virtual environment [2]. However, it has been observed that online learning, including video conference learning, lacks some of the metalanguage features that support classroom interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The outbreak forces many educational institutions to shift from traditional classroom-based learning to online learning [1] and hybrid learning is still maintained and conducted nowadays. Online video conferences have emerged as one of the most popular ways of providing face-to-face learning in a virtual environment [2]. However, it has been observed that online learning, including video conference learning, lacks some of the metalanguage features that support classroom interaction.…”
Section: Introductionmentioning
confidence: 99%